2023
DOI: 10.3389/fenvs.2022.1056268
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between environmental sustainability, good governance, financial inclusion, and tourism development in Bangladesh: Evidence from symmetric and asymmetric investigation

Abstract: Over the past decade, tourism’s contribution to economic Section progress has emerged as an alternative avenue for socio-economic development, especially in the productive economy with natural beauty. On the other hand, the potential effects of tourism on the environment have also been unveiled in the literature, along with macroeconomic misbehavior due to erratic environmental changes. However, the study’s impetus is to inspect the reaction of tourism contribution to Bangladesh’s economy from 1991–2019 with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 87 publications
4
34
0
Order By: Relevance
“…Foreign direct investment (FDI) is widely recognized as a major factor in economic growth through boosting output and capital formation, sharing expertise, becoming more marketable, and fostering macroeconomic stability. Most emerging and expanding countries now see attracting FDI as crucial to their economic development as a direct result of economic stability [ [2] , [3] , [4] , [5] ]. The beneficial effects of FDI on economic progress have been documented in diverse manners, including technological uplift, capital accumulation, operational efficiency, and human capital development, especially in developing nations.…”
Section: Figmentioning
confidence: 99%
“…Foreign direct investment (FDI) is widely recognized as a major factor in economic growth through boosting output and capital formation, sharing expertise, becoming more marketable, and fostering macroeconomic stability. Most emerging and expanding countries now see attracting FDI as crucial to their economic development as a direct result of economic stability [ [2] , [3] , [4] , [5] ]. The beneficial effects of FDI on economic progress have been documented in diverse manners, including technological uplift, capital accumulation, operational efficiency, and human capital development, especially in developing nations.…”
Section: Figmentioning
confidence: 99%
“…Moreover, this conclusion was supported by a large number of research that conducted temporal data analysis. Several nations, including Iran (11), India (12)(13)(14)(15)(16)(17)(18), Nigeria (19,20), and Pakistan, have reported that the impacts of economic expansion have been negative in their respective countries (21).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been conducted on the nexus between financial development and carbon emission to identify the potential channels through which economic development can affect carbon emission (13,22,23). The findings of these studies are mixed, with some finding a positive relationship and others finding a negative or no relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As technology advances and economies of scale come into play, the cost of producing clean electricity continues to fall, making it an increasingly attractive option for governments and businesses. All things considered; it's clear that increasing renewable energy consumption is one effective way we can mitigate climate change while promoting sustainable development worldwide (11,(19)(20)(21)(22)(23) Renewable energy consumption has the potential to reduce carbon emissions in Bangladesh significantly. As one of the most densely populated countries on earth, Bangladesh faces numerous challenges related to sustainable development, including high carbon emissions from traditional energy sources like coal and oil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, this conclusion was supported by a large number of research that conducted temporal data analysis. Several nations, including Iran (41), India (42)(43)(44)(45)(46)(47)(48), Nigeria (49,50), and Pakistan, have reported that the impacts of economic expansion have been negative in their respective countries (51).…”
Section: Literature Reviewmentioning
confidence: 99%